An integrative approach for understanding Islamic home financing adoption in Malaysia - Amin, Hanudin; Abdul Rahman, Abdul Rahim; Abdul Razak, Dzuljastri (Emerald Group Publishing Limited, 2013)
The purpose of this paper is to investigate the effects of subjective norm, relative advantage, simplicity, compatibility and perceived behavioural control on the Islamic home financing adoption. It also examines the effects of subjective norm, relative advantage, simplicity and compatibility on attitude. Analyses of attitude as a mediating factor are also provided.